Engineering a Clinically Translatable Bioartificial Pancreas to Treat Type I Diabetes. Issue 4 (April 2018) - Orive, Gorka; Emerich, Dwaine; Khademhosseini, Ali; Matsumoto, Shinichi; Hernández, R.M.; Pedraz, J.L.; Desai, Tejal; Calafiore, Riccardo; de Vos, Paul
Abstract : Encapsulating, or immunoisolating, insulin-secreting cells within implantable, semipermeable membranes is an emerging treatment for type 1 diabetes. This approach can eliminate the need for immunosuppressive drug treatments to prevent transplant rejection and overcome the shortage of donor tissues by utilizing cells derived from allogeneic or xenogeneic sources. Encapsulation device designs are being optimized alongside the development of clinically viable, replenishable, insulin-producing stem cells, for the first time creating the possibility of widespread therapeutic use of this technology. Here, we highlight the status of the most advanced and widely explored implementations of cell encapsulation with an eye toward translating the potential of this technological approach to medical reality. Highlights: Encapsulating insulin-secreting cells within implantable, semipermeable capsules is a potential approach for the treatment for type 1 diabetes that avoids or reduces the need for immunosuppressive drugs. Cells can be encapsulated in two distinct geometries, referred to as macro- and microcapsules. In macrocapsules, cells are immobilized in one relatively large device with the geometry of a hollow fiber, flat sheet, or disc. In microcapsules, cells are entrapped within a typically spherical hydrogel-based polymer, alginate being the most commonly used material in these systems. Alternative cell sources to conventional islets are being explored for the bioartificial pancreas. These may derive from xenogeneic sources, from hESCs, iPSCs, or β-cell-mimetic genetically engineered cells.